Financing vaccines in the 21st century : assuring access and availability - Institute of Medicine (U.S.). Committee on the Evaluation of Vaccine Purchase Financing in the United States (Washington, D.C. : National Academies Press, 2004)
The national immunization system has achieved high levels of immunization, particularly for children. However, this system faces difficult challenges for the future. Significant disparities remain in assuring access to recommended vaccines across geographic and demographic populations. These disparities result, in part, from fragmented public-private financing in which a large number of children and adults face limited access to immunization services. Access for adults lags well behind that of children, and rates of immunizations for those who are especially vulnerable because of chronic health conditions such as diabetes or heart and lung disease, remain low. "Financing Vaccines in the 21st Century: Assuring Access and Availability addresses these challenges by proposing new strategies for assuring access to vaccines and sustaining the supply of current and future vaccines. The book recommends changes to the Advisory Committee on Immunization Practices (AC1P)--the entity that currently recommends vaccines--and calls for a series of public meetings, a post-implementation evaluation study, and development of a research agenda to facilitate implementation of the plan.
Introduction -- Background -- Conceptual framework for the study -- Study process -- Summing up -- Organization of the report -- Origins and rationale of immunization policy -- Legislative history of vaccine policy -- Shared federal and state responsibility for financing -- Shared public and private responsibility for coverage -- Public and private delivery systems -- Private vaccine production -- The setting national of vaccine policy -- Findings -- Public and private insurance coverage -- Public insurance coverage -- Private insurance coverage -- Barriers to a well-functioning immunization finance system -- Findings -- The delivery system -- Delivery of adult and childhood vaccines -- The work of immunizing -- Provider reimbursement -- Barriers to a well-functioning immunization delivery system -- Findings -- Vaccine supply -- Size and growth of the vaccine market -- Vaccine production -- Cost structure -- Research and development -- Industry concentration -- Regulation -- Pricing -- Shortages -- Stockpiles -- CDC contracting -- Barriers to a well-functioning vaccine supply system -- Findings -- Conclusions and alternative strategies -- Conclusions -- Alternative strategies -- Weighing the alternatives -- Recommendations -- Final observations.
Includes bibliographical references (pages 211-220).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: United States -- Advisory Committee on Immunization Practices; Vaccination -- United States -- Planning; Vaccines -- Economic aspects -- United States; Vaccination -- Economic aspects -- United States; Vaccination -- Government policy -- United States; Pharmaceutical industry; Federal government; Mass Vaccination -- economics; Public Policy; Vaccines -- economics; Drug Industry; Federal Government; Financing, Government; Private Sector; Public Sector; United States; Vaccination -- États-Unis -- Planification; Vaccins -- Aspect économique -- États-Unis.; Vaccination -- Aspect économique -- États-Unis.; Vaccination -- Politique gouvernementale -- États-Unis.; Industrie pharmaceutique; Gouvernement fédéral.; Aide de l'État.; federal government; federal aid; MEDICAL -- Health Risk Assessment; MEDICAL -- Epidemiology; Pharmaceutical industry; Federal government; Vaccination -- Government policy; Vaccination -- Planning; Vaccines -- Economic aspects; United States